Contamination Prediction and Control of Landfills to Groundwater in Coalmine Subsidence Area. (February 2017) - Lin, Fei; Liu, Peigui; Wei, Ting; Ren, Honglei; Wu, Dan; Tao, Yuezan
Abstract: This paper aimed at the prediction and control of NH3 -N in the transportation of leachate under the monitored natural attenuation (MNA) of a landfill in the coalmine subsidence area of Huainan, Anhui province, China, and four scenarios were analyzed: (1) natural state without biodegradation, (2) natural state with biodegradation, (3) closure state without biodegradation, (4) closure state with biodegradation. The results showed that the leachate could be well controlled by anti-seepage wall and that the biodegradation played an important role in MNA process of NH3 -N in leachate. The feasibility of anti-seepage measures was put forward in terms of leachate control in landfill and conclusions according to the evaluation could be applied for actual contamination sites.